Unlocking the Potential of Liquid Plasma Polymer Films: Characterizing Aging Effects and Their Impact on the Wrinkling Phenomenon - Raut, Suyog A.; Vinx, Nathan; Tromont, David; Leclère, Philippe; Cossement, Damien; Snyders, Rony; Thiry, Damien (Langmuir, 2024)
Here, we present the study of the intricate dynamics between the physicochemical properties of liquid propanethiol plasma polymer films (PPFs) and the formation of wrinkles in PPF/Al bilayers. The study investigates the effect of liquid PPF aging in the air before top Al layer deposition by magnetron sputtering on the wrinkling phenomenon for 4 days. Thanks to atomic force microscopy, the wrinkle dimensions were found to decrease by approximately 55% in amplitude and 66% in wavelength, correlated with an increase in the viscosity of the PPF over the aging duration (i.e., from less than 107 to 1010 Pa·s). This behavior is not linked to alterations in cross-linking degree as evidenced by time-of-flight secondary ion mass spectrometry experiments but rather to network densification driven by the inherent molecular chain mobility due to the viscous state of the PPF. X-ray photoelectron spectroscopy measurements emphasizing the absence of oxidation of the PPF over the aging duration support this, revealing a unique aging mechanism distinct from other plasma polymer families. Overall, this study offers valuable insights into the design and application of mechanically responsive PPFs involved in bilayer systems, paving the way for advancements in nanotechnology and related fields.